Ανάπτυξη της ικανότητας των μαθητών της ΣΤ΄ τάξης του δημοτικού σχολείου να κατανοούν σύνθετες προγραμματιστικές έννοιες, μέσω της χρήσης παιγνιώδους προγραμματιστικού περιβάλλοντος - Μπούκλα, Κυριακή (2021)
Purpose: This project aims to investigate if the visual programming environment of Kodu, can help 6th grade primary students to understand complex programming concepts. Design / methodology / approach: For that purpose, a research was conducted in three different primary schools in Attica. From each school a sample of 21 students was selected; therefore, three different groups of students were created. The first group (group 0) used Kodu without following any instructions. The second group (group 1) was taught conventionally and the third group (group 2) was taught basic programming concepts with Kodu. After each lesson the performance of the students was evaluated. The evaluation of students was based in five basic programming terms: 1) the structure of the sequence, 2) programming concept AND, 3) variables, 4) programming concept IF / ELSE and 5) subroutines. Finally, a questionnaire was distributed only to the 2nd group for measuring their impressions using Kodu. Findings: The results indicated that Kodu enhanced the teaching process since the students of Group 2 demonstrated higher performance -in all the educational activities- compared with the students of the other groups. Additionally, the impressions of the pupils after using Kodu were positive, revealing that this tool that can be used systematically in primary education. Originality / value: The originality of this research is based on the fact that the effectiveness of Kodu in the Greek educational system has not been investigated systematically in the past.